The EFFECT OF RECIPROCAL TEACHING TECHNIQUE ON STUDENTS’ READING COMPREHENSION OF RECOUNT TEXT AT THE TENTH GRADE OFMAS BAITUR RAHMAN IN 2019/ 2020 ACADEMIC YEAR - kamisah S.Pd M.Pd (JURNAL LINER (Language Intelligence and Educational Research), 2019)
The objectives of the research are to find out: 1) the extent of the application of reciprocal teaching technique on students’ reading comprehension of recount text, 2) the extent of students’ reading comprehension of recount text before and after using reciprocal teaching technique, 3) whether there is any significant effect of reciprocal teachingtechnique on students’ reading comprehension of recount text at the tenth grade of MAS BaiturRahman. This research uses experimental method. The population is all the tenth grade students which are devided into two classes and total are 65 students. The sample consist of 29 students by using purposive sampling. The technique of collecting data is used observation and test. After collecting the data, the mean of application description reciprocal teaching technique is 3.6. It is catagorized “Very Good”. The students’ reading comprehension of recount text before using reciprocal teaching technique is 67.31 it is categorized “Enough” and after is 82.46 it is catagorized “Very Good”. The calculation of t-test formula is 10.47, and the t-table is 2.05. It means that there is a significant effect of reciprocal teaching technique on students’ reading comprehension of recount text at the tenth grade of MAS BaiturRahman.